Representasi Janda dalam Web series Terlanjur Sayang - Wiwid Adiyanto; Rr. Pramesthi Ratnaningtyas; Zairi Chairunnisa (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
The problem of the depiction of widows in the media cannot be separated from the discourse on gender inequality. The status of widows in the media tends to be presented homogeneously, namely that women are subordinated. This article explores the discourse construction and representation of widows in Indonesian web series. This research aims to describe the representation of widows broadcast in digital-based media with a focus on the web series Terlanjur Sayang. This research uses a narrative approach with Roland Barthes' semiological method which is supported by narrative analysis by Nick Lacey and Vladimir Propp as an analytical tool. Representation Theory is placed as an academic foundation. The results of the research show that widows are represented as people who are not financially independent, seducers of men, manipulative or deceitful, and people who are treacherous. The placement of widows in the narrative structure is positioned as a party that disturbs the balance and is the cause of social loss. This research also shows that widows are represented through women who colonize men with their symbolic capital. The web series Terlanjur Sayang gives rise to the myth of widows as people who pretend to be naïve.